Isolation and functional characterisation of honey bee gut bacteria with probiotic, antimicrobial, and antioxidant properties (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2026)
Probiotics are live microorganisms that confer health benefits to the host, particularly by modulating the gut microbiota. Honey bees possess a unique gut microbiome that may harbour novel probiotic strains with potential therapeutic applications. This study isolated and characterised probiotic bacteria from the gut of two honey bee species (Apis mellifera and Tetragonula iridipennis). Lactobacillus casei Shirota (Yakult) was used as a probiotic positive control. Out of the total isolates, 12 were analysed for probiotic traits, including bile and acid tolerance, starch and arginine hydrolysis, antimicrobial activity, beta-galactosidase activity, antioxidant activity, and adhesion ability. All isolates were negative for amylase and arginine dihydrolase but positive for Bile Salt hydrolase. Every isolate showed antibacterial activity, with three of them being more promising. Only 7 isolates demonstrated antifungal activity. Ten isolates were positive for β-galactosidase. Four isolates exhibited antioxidant activity comparable to that of the Lactobacillus casei Shirota. The control strain exhibited a hydrophobicity of 73.54%, while the highest hydrophobicity of 43.80% was observed in one of the gut isolates. Nine isolates exhibited apparent inhibitory effects against E. coli in non-neutralised supernatant, confirming that lactic acid is a potential antimicrobial substance. The isolates demonstrate potential probiotic properties based on in vitro evaluations, comparable to those of Lactobacillus casei Shirota.